Socioeconomic impact of COVID-19 restrictions in Bali: A nighttime light analysis - Putro, Dimas Hutomo; Pramana, Setia; Hendrawan, Daffa (Jurnal Ikatan Sarjana Ekonomi Indonesia, 2025)
This study investigates the socio-economic impacts of COVID-19 pandemic restrictions in Bali using nighttime light remote sensing as a proxy for socio-economic activity. The monthly NTL data from the Suomi-NPP VIIRS instrument, spanning from 2014 to 2021, are analyzed. This study focuses on changes in NTL trends before and after the restrictions, specifically the Large-Scale Social Restriction and Welfare Activity Restriction programs. To ensure that the NTL used in this study accurately measures human activity, we integrate the data with built-up area maps from the Global Human Settlement Layer. An ARIMA intervention model is employed to assess the impact of the restrictions on NTL, revealing a significant decrease in certain regions. Furthermore, we find a moderate correlation between NTL and Bali's quarterly GDP data. This study also highlights the potential of NTL remote sensing as a near-real-time proxy for socioeconomic change, allowing for the early evaluation of policy effectiveness. Keywords: nighttime light, COVID-19, proxy indicator, ARIMA intervention JEL Classification: C22; I18; R11